Comparative evaluation of buccal infiltration technique with buccal plus palatal infiltration technique using 4% articaine in patients with irreversible pulpitis of maxillary 1st molars: A prospective, randomized, In-Vivo study - Gufaran A Syed; Anuprabha Shrivastava; Suruchi Sisodia; Bhanupratap Sisodiya; Kanishk Gupta; Ahmed Saaduddin Sapri; Mohamed AboShetaih; Sulaiman Ibrahim S Alghamdi (Wolters Kluwer Medknow Publications, 2022)
Introduction: The purpose of this study was to evaluate and compare the buccal infiltration (BI) technique with the buccal plus palatal infiltration (BPI) technique using 4% articaine with 1:100,000 epinephrine. Methods: A total of 50 adult patients received BI, and the other 50 adult patients received BPI with 4% articaine with 1:100,000 epinephrine. During RCT procedure, when the patient experienced pain, the treatment was stopped and the extent of the procedure was documented. When a patient reported "no pain" (0 mm) or "weak/mild pain" (0 <= 54 mm), the anesthesia was considered successful. Results: Statistical analysis using unpaired t-test showed that the mean pain scores in both groups were comparable. Conclusion: The pain scores in both groups were comparable, but BI is better than BPI as a painful and traumatic palatal injection was avoided.